Gastrointestinal hemorrhage due to thinner neurofibroma: Surgical exploration - fibroscopic - Medina, Raúl; Torterolo, Edgardo; Estapé, Gonzalo; Lizaso, Isabel; de Mattos, Alfredo; de los Santos, Julio (Cirugía del Uruguay, 1980)
A patient suffering from Von Recklinghausen's disease had digestive hemorrhage of small intestine as a result of a neurofibroma of smair intestine. Laparotomy and resection of neurofibromas, assisted by intraoperatory fibroscopy of small intestine, were performed and postoperatory evolution was excellent.